2019
DOI: 10.1016/j.jwpe.2019.100868
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the effect of pore size of ceramic membranes on the pilot-scale removal of oil from oil-water emulsion

Abstract: Oil-water emulsions are one of the most serious pollutants because of the large quantities produced by various industries, such as the petrochemical, oil and gas industries. One of the major methods to remove oil from wastewater is filtration using ceramic tubular microfiltration membranes. However, such membranes are vulnerable to fouling, which causes operational impairment. The aims of this work are to study the influence of membrane pore size on permeate flux and oil removal efficiency at different operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 43 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…When the oil concentration in the oilwater emulsion is less or equal to 50 mg l −1 , it can be treated with a sand filter for satisfactory drinking water requirements. [188] The tubular configuration is the most frequently used membrane for the treatment of waste oil-in-water emulsion. A cellulose filter paper modified with PVA (cellulose-PVA) membrane is produced recently and applied for such separation.…”
Section: Economics Of Membrane Separation Of Oil In Water Emulsionsmentioning
confidence: 99%
“…When the oil concentration in the oilwater emulsion is less or equal to 50 mg l −1 , it can be treated with a sand filter for satisfactory drinking water requirements. [188] The tubular configuration is the most frequently used membrane for the treatment of waste oil-in-water emulsion. A cellulose filter paper modified with PVA (cellulose-PVA) membrane is produced recently and applied for such separation.…”
Section: Economics Of Membrane Separation Of Oil In Water Emulsionsmentioning
confidence: 99%
“…Almojjly, Johnson, and Hilal (2019) revealed that hybrid coagulation/sand filtration and ceramic microfiltration were the optimal condition for oil–water emulsion treatment. Based on a pilot study, the oil–water emulsion interacted with the surface of the ceramic membrane surface size, which indicated that the optimal pore size was depended on the concentration of oil in the emulsion and droplet size.…”
Section: Physical Processesmentioning
confidence: 99%
“…Almojjly, Johnson, and Hilal (2019) studied the impact of ceramic membrane pore size for the removal of oil–water emulsion, which was a major pollutant in wastewater industries. They used a hybrid coagulation/sand filter with microfiltration (MF) pretreatment process to investigate the pore size effect and oil removal efficiency.…”
Section: Chemical Processesmentioning
confidence: 99%
“…Currently, there are different technologies and methods for treating water polluted with oil, which takes into account the physical, physical–chemical, chemical, and biological principles that occur in the processes [ 4 , 6 ]. Among these methods are flotation [ 7 , 8 , 9 ], coagulation [ 6 , 10 , 11 , 12 , 13 ], the use of hydrocyclones [ 14 , 15 , 16 , 17 ], biological treatment [ 18 , 19 , 20 , 21 ] and membrane separation technologies [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Membrane separation processes can be classified into four categories according to the pore size: microfiltration, ultrafiltration, nanofiltration, and reverse osmosis [ 24 , 25 , 26 ]. The pore size of the membrane determines the filtration properties of water/oil emulsions, which can also vary, depending on the concentration of the oil in the emulsion and, consequently, on the size of the oil drop [ 13 , 27 ].…”
Section: Introductionmentioning
confidence: 99%